NANOEMULSION COMPONENTS SCREENING OF QUETIAPINE FUMARATE: EFFECT OF SURFACTANT AND CO SURFACTANT - Priya, Sneh; Koland, Marina; N, Suchetha Kumari (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Correct selection of oils, surfactants, and co surfactants along with their optimum concentration is essential to get stable and clinically acceptable nanoemulsions. The aim of the present study was, to provide an efficient screening approach for the excipients selection for the optimum nanoemulsion formulation development. Methods and Results: The solubility of quetiapine (QTP) fumarate in the oils (Capryol 90, isopropyl myristate, castor oil, and olive oil), surfactants (labrasol, cremophor EL, Brij L23, Tween 20, and Tween 80), and co surfactants (ethanol, isopropyl alcohol, and propylene glycol) was taken as the criterion for selection. The maximum solubility of QTP was found to 35.54±0.91, 40.4±0.83, and 32.07±0.92 in Isopropyl myristate, Tween 20, and propylene glycol, respectively. The effect of Tween 20/propylene glycol mass ratio on the nanoemulsion formation was also studied by varying the ratio from 3:1 to 1:0 for the further optimization of the system. The highest nanoemulsion region was obtained at Tween 20/propylene glycol in the mass ratio of 3:1. Formulations were selected from the phase diagram at which concentration of oil was constant with increasing (30, 35, 40, 45% wt/wt) concentration of surfactant/co surfactant mass ratio (Smix) and subjected to thermodynamic stability tests. The optimized formulations were characterized for particle size, viscosity, pH and refractive index measurements. All the selected formulations were found to be stable, and the droplet size was found to be <100 nm. Conclusion: The formulations were thermodynamically stable and can be effectively used for the drug delivery applications.